Simulation and Optimization of Temperature Effect in Solar Cells CdTe with Back Connection Cu2O - Khaledi, Parinaz; Behboodnia, Mahdi; Karimi, Mohammad (International Journal of Optics, 2022)
One of the least studied and most important parameters that are ignored in the simulation and construction of solar cells is temperature. The effect of temperature is complex, and the solar cell is a very temperature-sensitive device. Constructing high-efficient solar cells is an essential task. In this paper, we simulated and studied the effect of temperature on the characteristics of FTO/SnO2/CdS/CdTe/Cu2O solar cells using MATLAB and Maple software. For this purpose, first, the transport and Poisson equations, the continuity of the current, and the transfer of the carrier were solved by the drift-diffusion method and then they were discretized. We examined the cell temperature in the range of 200 to 400 Kelvin. The results showed that increasing temperature from 200 to 400 Kelvin open-circuit voltage decreases the short-circuit current. Furthermore, the filling factor first increases and then decreases. The efficiency of the solar cell also decreases sharply with increasing temperature. The results showed that, by decreasing the temperature of the solar cell, an efficiency of more than 32% can be achieved in cadmium telluride solar cells with FTO/SnO2/CdS/CdTe/Cu2O structure.